Myocardial matrix hydrogel acts as a reactive oxygen species scavenger and supports a proliferative microenvironment for cardiomyocytes. (15th October 2022) - Wang, Raymond M.; Mesfin, Joshua M.; Hunter, Jervaughn; Cattaneo, Paola; Guimarães-Camboa, Nuno; Braden, Rebecca L.; Luo, Colin; Hill, Ryan C.; Dzieciatkowska, Monika; Hansen, Kirk C.; Evans, Sylvia; Christman, Karen L.
Abstract: As the native regenerative potential of adult cardiac tissue is limited post-injury, stimulating endogenous repair mechanisms in the mammalian myocardium is a potential goal of regenerative medicine therapeutics. Injection of myocardial matrix hydrogels into the heart post-myocardial infarction (MI) has demonstrated increased cardiac muscle and promotion of pathways associated with cardiac development, suggesting potential promotion of cardiomyocyte turnover. In this study, the myocardial matrix hydrogel was shown to have native capability as an effective reactive oxygen species scavenger and protect against oxidative stress induced cell cycle inhibition in vitro . Encapsulation of cardiomyocytes demonstrated an enhanced turnover in in vitro studies, and in vivo assessments of myocardial matrix hydrogel treatment post-MI showed increased thymidine analog uptake in cardiomyocyte nuclei compared to saline controls. Overall, this study provides evidence that properties of the myocardial matrix material provide a microenvironment mitigating oxidative damage and supportive of cardiomyocytes undergoing DNA synthesis, toward possible DNA repair or cell cycle activation. Statement of significance: Loss of adult mammalian cardiomyocyte turnover is influenced by shifts in oxidative damage, which represents a potential mechanism for improving restoration of cardiac muscle after myocardial infarction (MI). Injection of a myocardial matrix hydrogel into the heart post-MI previously demonstrated increased cardiac muscle and promotion of pathways associated with cardiac development, suggesting potential in promoting proliferation of cardiomyocytes. In this study, the myocardial matrix hydrogel was shown to protect cells from oxidative stress and increase proliferation in vitro. In a rat MI model, greater presence of tissue free thiol content spared from oxidative damage, lesser mitochondrial superoxide content, and increased thymidine analog uptake in cardiomyocytes was found in matrix injected animals compared to saline controls. Overall, this study provides evidence that properties of the myocardial matrix material provide a microenvironment supportive of cardiomyocytes undergoing DNA synthesis, toward possible DNA repair or cell cycle activation. Graphical abstract: Image, graphical abstract